Cardiovascular risk and complications associated with COVID-19 - Krittanawong, Chayakrit (Am J Cardiovasc Dis, 2020)
In December 2019, an unprecedented outbreak of pneumonia cases associated with acute respiratory distress syndrome (ARDS) first occurred in Wuhan, Hubei Province, China. The disease, later named Coronavirus disease 2019 (COVID-19) by the World Health Organization (WHO), was caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2), and on January 30, 2020, the WHO declared the outbreak of COVID-19 to be a public health emergency. COVID-19 is now a global pandemic impacting more than 43,438,043 patients with 1,158,596 deaths globally as of August 26th, 2020. COVID-19 is highly contagious and has caused more deaths than SARS in 2002-2003 or the Middle East Respiratory Syndrome (MERS) in 2012-2013 combined and represents an unprecedented human affliction not seen since the influenza pandemic of 1918. COVID-19 has been associated with several cardiac complications, including hypercoagulability, acute myocardial injury and myocarditis, arrhythmias, and acute coronary syndromes. Patients with pre-existing cardiovascular disease (CVD) are at the highest risk for myocardial injury and mortality among infected patients. The mechanism by which COVID-infected patients develop cardiac complications remains unclear, though it may be mediated by increased ACE-2 gene expression. Despite initial concerns, there is no evidence that angiotensin-converting enzyme (ACE) inhibitor or angiotensin receptor blocker (ARB) therapy increases risk for myocardial injury among those infected with COVID-19. In the current report, we summarize the peer-reviewed and preprint literature on cardiovascular risks and complications associated with COVID-19, as well as provide insights into its pathogenesis and management.